The Paleozoic evolution of the Andes and its foreland: Introduction - Serra Varela, Samanta (2023)
In the southern part of the Andean Cordillera and nearby areas of its foreland, located in the Bolivian, Chilean and Argentinian territory, there are Paleozoic basement relicts of variable extension, which formed part of the W and SW margin of Gondwana. This basement has been involved in orogenic events prior to the Andean orogeny (active from the Cretaceous to the present), some of which starts in the Neoproterozoic or reach the beginning of the Mesozoic. During the Paleozoic and according to Heredia et al. (2016, 2018), a set of continental fragments of variable extent and allochtony was successively accreted to the Gondwana margin, resulting in six Paleozoic orogenies of different temporal and spatial extension: Pampean (Ediacaran-early Cambrian), Famatinian (Middle Ordovician-Silurian), Ocloyic (Middle Ordovician-Devonian), Chanic (Middle Devonian-early Carboniferous), Gondwanan (Middle Devonian-middle Permian) and Tabarin (late Permian-Triassic). All these orogenies culminate with collisional events, with the exception of the Tabarin and the Gondwanan north of 39º S that are subduction-related.